2019
DOI: 10.1002/jbmr.3713
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in The Rotterdam Study: About Muscle Mass, Sarcopenia, Fat Mass, and Fat Distribution

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide. Obesity is a major risk factor for NAFLD and recently, low skeletal muscle mass emerged as additional risk factor for NAFLD. However, the different contributions of body mass index (BMI) to the risk of NAFLD are not yet well‐known. We therefore studied body composition and muscle function with NAFLD in an elderly population‐based study. Participants of European descent underwent dual‐energy X‐ray absorptiometry (DXA) and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
5
71
0
Order By: Relevance
“…However, recommending or performing liver biopsy in presumably healthy individuals could raise an ethical concern, considering that this study exclusively enrolled health checkup examinees. Second, the bioelectrical impedance analyzer used in this study was unable to determine the distribution (android or gynoid) of the fat mass, which is known to be related to metabolic abnormalities and NAFLD 19,33 . In addition, assessment of visceral adiposity, such as abdominal fat computed tomography, was unavailable.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, recommending or performing liver biopsy in presumably healthy individuals could raise an ethical concern, considering that this study exclusively enrolled health checkup examinees. Second, the bioelectrical impedance analyzer used in this study was unable to determine the distribution (android or gynoid) of the fat mass, which is known to be related to metabolic abnormalities and NAFLD 19,33 . In addition, assessment of visceral adiposity, such as abdominal fat computed tomography, was unavailable.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, our results indicated that high baseline fat mass was a better predictor for incident NAFLD than low muscle mass in the normal-weight, overweight, and obese groups. From the Rotterdam study of a large population-based cohort, cross-sectional analysis showed that both high fat mass and low muscle mass were associated with NAFLD in normal-weight women (BMI < 25), whereas fat mass was a better predictor for NAFLD prevalence in both sexes 19 . Likewise, our results suggested that relative excess of fat mass predicted incident NAFLD better in all study populations except in participants with BMI < 18.5, whereas low muscle mass was only significant in the normal-weight subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies have already demonstrated a positive relationship between sarcopenia and the prevalence of NAFLD [6,11,19,20]. Hong et al rstly found the OR for NAFLD risk was 5.16 (95%CI 1.63-16.33) in the lowest quartile of SMI compared to the highest quartile [6].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectations, subjects with higher processed meat consumption registered lower liver stiffness values, while previous studies indicated that processed meat consumption was associated with an increased risk of chronic liver disease [43]. This result might be explained since transient elastography is a technique to assess the presence of advanced fibrosis or cirrhosis [44] and according to several authors, the cut-off point in order to determine liver fibrosis ranges from 6.5 to 8 kPa [6,45,46,47]. Our study population presented lower liver stiffness values, suggesting that participants did not present hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%